Pengaruh Inklus Keuangan, Fintech Payment Gateway dan Money Attitude Terhadap Pengelolaan Keuangan Pada Generasi Z Di Kota Denpasar - Ni Komang Lusi Arianti; G.A. Desy Arlita; Putu Sri Arta Jaya Kusuma; I Gusti Agung Ayu Pramita Indraswari (Ikatan Da'i Indonesia, 2025)
The objectives of this study were: 1) to determine the effect of financial inclusion on financial management among Generation Z in Denpasar. 2) to determine the effect of fintech payment gateways on financial management among Generation Z in Denpasar. 3) to determine the effect of money attitudes on financial management among Generation Z in Denpasar. This study used three independent variables: financial inclusion, fintech payment gateways, and money attitudes, with one dependent variable: financial management. This study was conducted in Denpasar. Data collection used a questionnaire. The sample size was 100 respondents, comprising Generation Z in Denpasar, using a saturated sampling method. The data obtained were then processed and analyzed using multiple linear regression analysis.The data analysis found that: 1) financial inclusion has a positive and significant effect on financial management among Generation Z in Denpasar. 2) fintech payment gateways have a positive and significant effect on financial management among Generation Z in Denpasar. 3) money attitudes have a positive and significant effect on financial management among Generation Z in Denpasar.